Recognition of histone acetylation by the GAS41 YEATS domain promotes H2A.Z deposition in non-small cell lung cancer - Hsu, Chih-Chao; Shi, Jiejun; Yuan, Chao; Zhao, Dan; Jiang, Shiming; Lyu, Jie; Wang, Xiaolu; Li, Haitao; Wen, Hong; Li, Wei; Shi, Xiaobing (Genes & development, 2018)
Histone acetylation is associated with active transcription in eukaryotic cells. It helps to open up the chromatin by neutralizing the positive charge of histone lysine residues and providing binding platforms for “reader” proteins. The bromodomain (BRD) has long been thought to be the sole protein module that recognizes acetylated histones. Recently, we identified the YEATS domain of AF9 (ALL1 fused gene from chromosome 9) as a novel acetyl-lysine-binding module and showed that the ENL (eleven-nineteen leukemia) YEATS domain is an essential acetyl-histone reader in acute myeloid leukemias. The human genome encodes four YEATS domain proteins, including GAS41, a component of chromatin remodelers responsible for H2A.Z deposition onto chromatin; however, the importance of the GAS41 YEATS domain in human cancer remains largely unknown. Here we report that GAS41 is frequently amplified in human non-small cell lung cancer (NSCLC) and is required for cancer cell proliferation, survival, and transformation. Biochemical and crystal structural studies demonstrate that GAS41 binds to histone H3 acetylated on H3K27 and H3K14, a specificity that is distinct from that of AF9 or ENL. ChIP-seq (chromatin immunoprecipitation [ChIP] followed by high-throughput sequencing) analyses in lung cancer cells reveal that GAS41 colocalizes with H3K27ac and H3K14ac on the promoters of actively transcribed genes. Depletion of GAS41 or disruption of the interaction between its YEATS domain and acetylated histones impairs the association of histone variant H2A.Z with chromatin and consequently suppresses cancer cell growth and survival both in vitro and in vivo. Overall, our study identifies GAS41 as a histone acetylation reader that promotes histone H2A.Z deposition in NSCLC.